Estimating Vegetation Density Changes, Tree Diversity, and Carbon Stock in Eduforest, Bekasi Regency, West Java, Indonesia - Hartoyo, Adisti Permatasari Putri; Muhammad, Dimas Nur; Madani, Hilmi Naufal (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Climate change poses a threat in the form of temperature elevation, which can alter weather patterns and ecological balance, necessitating urgent mitigation strategies, such as emission reduction and enhanced carbon sequestration in the urban forest. This research aimed to analyse vegetation density through the NDVI approach, assess tree stand structure and composition, and approximate aboveground carbon stocks in the urban forest, specifically in Eduforest, Bekasi Regency, Indonesia. The methodology involved vegetation analysis and carbon stock estimation, utilising allometric and destructive estimation for seedling and understory levels. The high-density class in Eduforest had the highest area increase in 2023, from 0.64 ha in 2013 to 1.31 ha in 2023. There are 36 species found in all growth levels and the understory. The dominant species, such as Swietenia mahagony, Acacia mangium, and Falcataria falcata, are fast-growing. The tree-growth level has the highest carbon stock (39.90 tons/Ha) of the other growth levels. Eduforest can be an alternative effort to maintain vegetation diversity and carbon stock in addressing climate change.